Efficacy of nutraceutical supplements containing Passiflora incarnata L., Withania somnifera (L.) Dunal and Taraxacum officinale (L.) weber ex F.H.Wigg. on markers of inflammation, oxidative stress and gut microbiota in senior dogs - Ciarcia, Roberto; Longobardi, Consiglia; Iervolino, Valeria; Manenti, Tommaso; Ferrucci, Francesco; Veneruso, Iolanda; D’Argenio, Valeria; Rubino, Antonio; Pelagalli, Alessandra; Lombardi, Pietro; Damiano, Sara (Frontiers in Veterinary Science, 2025)
IntroductionAging in dogs is a complex phenomenon characterized by metabolic, immunological and neurological alterations that may result in chronic inflammation, oxidative stress, and intestinal microbiota changing that can compromise dogs’ overall health. Phytotherapeutics represents a promising approach to improve the quality of life in elderly dogs. In this study we have tested a mix of phytoextracts on seven old breed dogs to evaluate their synergistic beneficial effects.MethodsThe mix was constituted by Passiflora incarnata (4% vitexin), Withania somnifera (2.5% withanolides), and Taraxacum officinale (20% inulin) administered per os for 40 days in addition to their diet. The whole blood and serum have been collected at the beginning of the experimental phase (T0), after 20 days (T1) and at the end point of the experiment, i.e., 40 days (T2), and used for biochemical analysis, detection of interleukins by ELISA, and for malondialdehyde (MDA) and Total antioxidant capacity (TAC) assay. Fresh feces have been collected at the same time points and immediately frozen to evaluate gut microbiota modification by 16S rRNA sequencing.ResultsResults revealed a significant reduction of C-reactive protein (CRP) for T1 and T2 respect to the basal condition (T0) (p < 0.05). Moreover, a statistical decrease in IL-6 and IL-10 cytokines at both T1 and T2 was observed, probably due to mitigation of chronic inflammation in the treated old dogs. The addition of the abovementioned extracts into the diet was associated with TAC increase and reduced lipid peroxidation in the sera of aged dogs, especially at T2 (p < 0.01). After treatment, an interesting modulation of the microbiota was observed with a trend from T0 to T2 toward higher relative abundances of SCFA-producing taxa, although alpha and beta diversity metrics did not reach statistical significance.DiscussionThis study supports the hypothesis that the integration of these herbal medicines into dietary or therapeutic regimens could represent a natural and synergistic strategy to improve the quality of life, promoting the general well-being of old dogs.